Implementasi Teknologi Dalam Pendidikan Pada Pembelajaran Hybrid Di Sekolah SMP Negeri 85 Jakarta Dan SMA Negeri 34 Jakarta - Isa Azizah Ramadhani; Riovaldi Paruntungan Silalahi; Stefie Yuliandra; Nirindah Daniella Sembiring; Frisca Adelia Stevani; Syahla Pridehan; Muhammad Faqih Al-Anshari; Velissa Maharani; Dimas Dimyati (Pusat Riset dan Inovasi Nasional, 2024)
The advancement of science and technology and the changes that have taken place have given rise to a new awareness that Indonesia no longer stands alone. Indonesia is in the middle of a vast and modern world, an open world so that people are free to compare life with other countries. The rapid development of information technology in the current era of globalisation is inevitable in its influence on the world, especially in the world of education. This study aims to determine the development of science and technology in the school environment, to determine the impact of technological developments in education, to determine the role of technology in supporting learning in schools, and to determine the development of technology in schools SMPN 85 Jakarta and SMAN 34 Jakarta. This type of research uses a qualitative approach. Qualitative research is descriptive research and tends to use analysis. Process and meaning are emphasised in this research. The theoretical foundation is used as a guide so that the focus of the research is in accordance with the facts in the field. The results of the research issued in the form of articles are written works that contain opinions or opinions of writers on problem issues, which aim to inform, influence, and convince readers. Posters, image media that combine visual elements such as lines, images, and words that can attract attention. At this stage our team will create a poster that contains the essence of the problem we are researching, and video documentation. Documentary, a work that leads to something real, factual, by recording the reality of an event. At this stage our team will record everything that happens in the field such as interviewing students about the development of science and technology in their school.